Proses Pembinaan Akhlak Di Sekolah Sebagai Implementasi Manajemen Pendidikan Islam - Bashirotul Hidayah; Muhammad Asrori Ma’sum; Ninik Nikmatul Fikriyah (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2021)
A good educator is one who is not only concerned with fulfilling obligations to the institution but more importantly paying attention to and fostering the morals of his students. The highest dedication of an educator is not only seeing the success and high knowledge of his students but more than that, educators are considered perfect success if their students have good character and morals in the midst of society. This is one thing that cannot be denied, which is often overlooked and even forgotten by educators today, that a student is not only thirsty for IQ (Intelligence Quotients), but also needs guidance and assistance in managing EQ (Emotional Quotients) and SQ (Spirirtual Quotients). . This is where the author is interested in bringing up the process of character education in schools carried out by SMP Negeri 1 Mojoagung Jombang.